PENGARUH PENAMBAHAN KARBOKSIMETIL SELULOSA DAN AGAR-AGAR TERHADAP FISIKOKIMIA DAN SENSORI FRUIT LEATHER BUAH MERAH (Pandanus conoideus Lamk) - Santoso, Budi (Jurnal Agroindustri, 2024)
The solid waste extracted from red fruit oil still contains nutrients which can be processed into various food products, one of which is fruit leather. This study aimed to evaluate the addition of emulsifiers, namely Carboxy Methyl Cellulose (CMC) and agar powder on the physicochemical and sensory characteristics of fruit leather of red fruit. This study was designed using a completely randomized design with two replications. The fruit leather was made in four treatments, F1 (CMC 0.25%), F2 (0.25% agar), F3 (0.15% CMC and 0.15% agar-agar), and F4 (0.25% CMC and agar-agar 0.25). Observations on the four fruit leather formulas were carried out on physicochemical properties, namely color, total dissolved solids (TDS) and moisture content, sensory tests (ranking tests and hedonic tests) include color, aroma, taste, and elasticity, proximate and bioactive components (total carotenoids and tocopherols). The results showed that the physical characteristics of red fruit leather from the four formulas had a red to dark red color, TDS ranged from 42.4-48.0 °Brix, and moisture content ranged from 10.26-12.87%, which met the standard National for intermediate moisture products. The use of CMC and agar powder in general does not remove the distinctive aroma and taste of red fruit and also the level of elasticity was good enough so that the fruit leather of red fruit can be rolled properly. In addition, the overall color, aroma, taste, and elasticity of all fruit leather formulations were acceptable to the panelists. The best fruit leather formula was F3, with a composition of red fruit pulp 60.2%, 0.15% CMC, 0.15% agar powder, 0.2% citric acid, 10% sugar, and 29.3% water; which proximate content, namely ash content 1.29% (db), fat 28.38% (db), protein 0.29% (db), carbohydrates 55.63% (db) and total dissolved solids 48,0 oBrix; as well as bioactive components, namely total carotenoids 1,365 ppm and total tocopherols 553 ppm.